Analisis Penerapan Model Flipped Classroom dalam Pembelajaran Pendidikan Jasmani: Systematic Literatur Review - Irfan Putra Muda; Citra Azhariat Malasari (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine the effectiveness of the implementation of the flipped classroom model in physical education learning. The method used is a Systematic Literature Review (SLR) by selecting and synthesizing eleven articles that met the inclusion criteria from 2019–2024, obtained from SINTA and Google Scholar databases. The results show that the implementation of the flipped classroom model has a positive impact on learning outcomes, independence, motivation, critical thinking skills, and the effectiveness of the physical education learning process. In conclusion, the flipped classroom model is an innovative learning approach that is feasible to be implemented to improve the quality of physical education learning in the digital era, considering teacher readiness, technology access, and students’ digital literacy.   Keywords: Flipped Classroom, Physical Education